Academic freedom as a defensive right - Stachowiak-Kudła, Monika (2023)
Ensuring the proper implementation of academic freedom can be difficult both for policymakers and university authorities. Hence, great emphasis should be given to the defensive function of academic freedom. In this paper, we analyse the legal regulations and the jurisprudence of the constitutional courts of Germany, Hungary, Poland, Portugal, and Spain. We identify who is the holder of academic freedom, how the defensive function of academic freedom works and what academic activities are being protected. The study shows that individual countries emphasise slightly different aspects of the defensive function of academic freedom but remain unanimous on the essence of this function. As academic freedom is not defined unequivocally in most constitutions and legal frameworks, constitutional courts play a significant role in shaping its defensive function.